Exploring The Barriers of Biology Education Students in Writing Scientific Papers - Dyah Aniza Kismiati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Scientific papers at this time are something that must be mastered by a student. Scientific articles produced by someone contribute new knowledge to the world of Education. This study aims to analyze the obstacles experienced by students when writing scientific articles. The research was conducted on biology education students at the Open University who are in their final semester and take scientific work courses as one of the graduation requirements. There were at least 13 students who were the research samples taken purposively. To obtain data, the researcher provided a questionnaire and conducted interviews with a sample of students. The data were then analyzed descriptively and resulted in the discovery that the main barriers of biology education students in writing scientific papers are lack of student experience in writing scientific papers especially in the components of scientific papers. They found it difficult when creating an introduction (54%), method (46%), and presenting results and discussions (54%). The recommendation from this study is the need to develop learning strategies in scientific work courses that can train students to get used to developing ideas and process these ideas into original articles and free from plagiarism.